GluN2B inhibition rescues impaired potentiation and epileptogenicity at associational-commissural CA3 synapses in a model of anti-NMDAR encephalitis. (31st January 2023) - Küpper, Maraike; Porath, Katrin; Sellmann, Tina; Bien, Christian G.; Köhling, Rüdiger; Kirschstein, Timo
Highlights: High-frequency stimulation potentiates associational-commissural CA3 synapses. Potentiation is reduced in slices from anti-NMDAR-treated animals. Ro 25–6981 restores potentiation in slices from anti-NMDAR-treated animals. Ro 25–6981 reduced also epileptiform afterpotentials. Abstract: Anti- N -methyl-d -aspartate receptor (anti-NMDAR) encephalitis is an autoimmune epilepsy associated with memory deficits. Research has demonstrated that anti-NMDAR inhibit long-term potentiation, and, at the same time, lead to disinhibition in the form of epileptiform afterpotentials in the potentiated state. While both effects may give rise to the key symptoms of the disease, the molecular basis of being simultaneously inhibitory and disinhibitory is difficult to explain. Here, we explored a possible involvement of the GluN2B subunit. To this aim, we injected cerebrospinal fluid from anti-NMDAR encephalitis patients into the rat hippocampus and prepared brain slices for in vitro field potential recordings. Associational-commissural-fiber-CA3 synapses from anti-NMDAR-treated animals showed increased field potential amplitudes with concomitantly enhanced paired-pulse ratios as compared to control tissue. GluN2B inhibition by Ro 25–6981 mimicked these effects in controls but had no effect in anti-NMDAR tissues indicating a presynaptic and occluding effect of anti-NMDAR. We then induced potentiation of associational-commissural-fiber-CA3 synapses, and confirmed that slices from anti-NMDAR-treated animals showed reduced potentiation and pronounced epileptiform afterpotentials. Intriguingly, both effects were absent when Ro 25–6981 was added in vitro before inducing potentiation. These results indicate that GluN2B-containing NMDARs, partially expressed presynaptically, show differential sensitivity to anti-NMDAR, and that altered GluN2B function is particularly apparent in the potentiated state rather than under baseline conditions. Since GluN2B inhibition rescued the effects of anti-NMDAR in the potentiated state, this opens the possibility that at least a subgroup of patients could benefit from a GluN2B antagonist.